Lanthanide metal–organic frameworks: Structural, thermal and sorption properties - Renata Łyszczek; Liliana Mazur; Agnieszka Ostasz; Agata Bartyzel; Halina Głuchowska (Adsorption Science & Technology)
Two coordination polymers of erbium(III) and neodymium(III) ions with 1,3,5-benzenetricarboxylic acid were synthesized under the solvothermal conditions from the dimethylformamide solution. They were characterized by the attenuated total reflectance Fourier transform spectroscopy (ATR-FTIR), thermogravimetry and differential scanning calorimetry (TG-DSC), thermogravimetric analysis coupled with Fourier transform infrared spectroscopy (TG-FTIR) and X-ray diffractions methods. The single-crystal X-ray analysis confirmed formation of three-dimensional framework of Er(III) 1,3,5-benzenetricarboxylate with the channels occupied by dimethylformamide and water molecules. Porosity of crystalline complexes was investigated by the nitrogen sorption experiments. The Nd and Er compounds exhibit real porosity with the BET surface area of 259 and 225 m 2 /g, respectively. The Horvath–Kawazoe analysis of pore-size distributions for the obtained complexes points out to their microporous character.